The Incidence of Propionibacterium acnes in Open Shoulder Surgery: A Controlled Diagnostic Study - Mook, William R; Klement, Mitchell R; Green, Cynthia L; Hazen, Kevin C; Garrigues, Grant E (Journal of bone and joint surgery. American volume, 2015)
Propionibacterium acnes has arisen as the most common microorganism identified at the time of revision shoulder arthroplasty. There is limited evidence to suggest how frequently false-positive cultures occur. The purpose of this prospective controlled study was to evaluate culture growth from specimens obtained during open shoulder surgery. Patients undergoing an open deltopectoral approach to the shoulder were prospectively enrolled. Patients with a history of shoulder surgery or any concern for active or previous shoulder infection were excluded. Three pericapsular soft-tissue samples were taken from the shoulder for bacterial culture and were incubated for fourteen days. A sterile sponge was also analyzed in parallel with the tissue cultures. In addition, similar cultures were obtained from patients who had undergone previous shoulder surgery. Overall, 20.5% of surgeries (twenty-four of 117) yielded at least one specimen removed for culture that was positive for bacterial growth, and 13.0% of sterile control specimens (seven of fifty-four) had positive culture growth (p = 0.234). P. acnes represented 83.0% of all positive cultures (thirty-nine of forty-seven) at a median incubation time of fourteen days. Among the subjects who had not undergone previous surgery, 17.1% (fourteen of eighty-two) had at least one positive P. acnes culture. Male sex was univariably associated with a greater likelihood of bacterial growth (p < 0.01), and patients who had not undergone previous surgery and had received two or more preoperative corticosteroid injections had a higher likelihood of bacterial growth (p = 0.047). The clinical importance of positive P. acnes cultures from specimens obtained from open shoulder surgery remains uncertain. Male sex and preoperative corticosteroid injections were associated with a higher likelihood of bacterial growth on culture and are risk factors that merit further investigation. Previously reported incidences of positive P. acnes culture results from specimens from primary and revision shoulder arthroplasty may be overestimated because of a substantial level of culture contamination. P. acnes is isolated via culture at a substantial rate from shoulders undergoing a deltopectoral approach. The clinical importance of culture growth by this low-virulence organism still remains uncertain. Further study is necessary to more specifically characterize culture growth by P. acnes as an infection, commensal presence, or contaminant.